1999
DOI: 10.1002/(sici)1522-2586(199902)9:2<187::aid-jmri6>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Do T2‐weighted pulse sequences help with the differential diagnosis of enhancing lesions in dynamic breast MRI?

Abstract: In this study, our purpose was to determine whether T2-weighted images are a useful diagnostic adjunct for lesion characterization in dynamic breast MRI. On a 1.5-T system, 205 enhancing benign and malignant breast tumors were examined. The standardized protocol consisted of a T2-weighted turbo spin echo (TSE) pulse sequence with and without spectral fat suppression (SPIR), followed by a two-dimensional dynamic series with subtraction postprocessing. In 59 cases, T2*-weighted gradient-echo images also were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
3
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 0 publications
3
47
3
1
Order By: Relevance
“…Thus sensitivity of T2WI to detect malignant lesions was found to be 95%, specificity being 80.6%.This is in accordance with studies conducted by Kuhl et al, (1) in which majority (87%) malignant lesions were isointense or hypointense on T2WI. Malich et al, (2) concluded that most malignant lesions were hypointense on T2WI.…”
Section: Signal Intensity On T2wisupporting
confidence: 88%
“…Thus sensitivity of T2WI to detect malignant lesions was found to be 95%, specificity being 80.6%.This is in accordance with studies conducted by Kuhl et al, (1) in which majority (87%) malignant lesions were isointense or hypointense on T2WI. Malich et al, (2) concluded that most malignant lesions were hypointense on T2WI.…”
Section: Signal Intensity On T2wisupporting
confidence: 88%
“…This is classically considered to be a clear sign of fibroadenoma [25]; however, this finding has recently been questioned, with T 2 hypersignals described in several breast cancers including (predominantly) mucinous carcinomas, invasive ductal carcinomas, metaplastic carcinomas and intracystic papillary carcinomas [26,27]. In our experience ( Figure 5), as in the cases reported in these studies, the mass on T 2 weighted sequences generally does not have a homogeneous hyperintense sequence, whereas, in fibroadenomas, the hyperintense signal is homogeneous, except where there are thin septa [28].…”
Section: Massmentioning
confidence: 99%
“…Despite positives in sensitivity, MRI lacks in specificity, making it difficult for clinicians to stage cancers. This difficulty adds unnecessary obstacles in the treatment process [4]. Other popular methods such as X-ray computed tomography (CT) have similar problems in staging due to low resolution, even with the use of contrast agents [5,6].…”
Section: Introductionmentioning
confidence: 99%